Development of CANDU-specific operational intervention levels. (April 2022) - Lebel, Luke; Shah, Manit; Chouhan, Sohan; Brown, Morgan; Morreale, Andrew; Edwards, Geoff; Korolevych, Volodymyr
Highlights: Development of CANDU-specific operational intervention levels. Extension of IAEA methodology from EPR-NPP-OILs (2017). Based on postulated releases from CANDU reactor and irradiated fuel bay accidents. CANDU OILs largely consistent with LWR OILs, expect for OIL7 for food post analysis. Shortcomings for OIL7 addressed by including 106 Ru as extra marker radionuclide. Abstract: Operational intervention levels (OILs) are measurement-based criteria to indicate whether the prompt implementation of protective response actions (e.g.,  evacuation, relocation, food restrictions) should be undertaken in a nuclear emergency. The IAEA published a new set in 2017 based on light water reactors, while the uncertainties on whether they could be applicable to CANDU reactors (which have different fuel burn-up and severe accident progression characteristics) are addressed in this study. By and large, the CANDU-specific OIL(t, mix) function values were similar to the light water reactor-based IAEA values. One exception was OIL7 for food restrictions, which required that an additional marker radionuclide, 106 Ru, be considered in addition to 131 I and 137 Cs, to reduce the uncertainty of the OIL. The CANDU-specific OIL values that result from this study will help to inform national authorities on how to adapt OILs to the emergency response arrangements in Canada and other countries operating CANDU reactors.